2019
DOI: 10.1257/pol.20180510
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Inequality through Dynamic Complementarity: Evidence from Head Start and Public School Spending

Abstract: We compare the adult outcomes of cohorts who were differentially exposed to policy-induced changes in Head Start and K–12 spending, depending on place and year of birth. IV and sibling-difference estimates indicate that, for poor children, these policies both increased educational attainment and earnings, and reduced poverty and incarceration. The benefits of Head Start were larger when followed by access to better-funded schools, and increases in K–12 spending were more efficacious when preceded by Head Start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 54 publications
2
57
1
Order By: Relevance
“…Johnson and Jackson (2019) analyzed earlier cohorts of siblings born before 1976 with a dynamic complementarity design (i.e., capitalizing on two exogenous sources of variation separated in time). They found a larger, more precise estimate: Attending Head Start at age 4—that is, facing an average Head Start spending versus no spending, coupled with (and sensitive to) an average public K–12 spending—boosted earnings of poor children (measured from age 20–50) by 0.10 log points ( SE = 0.02).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson and Jackson (2019) analyzed earlier cohorts of siblings born before 1976 with a dynamic complementarity design (i.e., capitalizing on two exogenous sources of variation separated in time). They found a larger, more precise estimate: Attending Head Start at age 4—that is, facing an average Head Start spending versus no spending, coupled with (and sensitive to) an average public K–12 spending—boosted earnings of poor children (measured from age 20–50) by 0.10 log points ( SE = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“… 2. For example, Johnson and Jackson (2019) calculated that for a child attending Head Start, a 10% increase in K–12 spending boosted educational attainment by 0.4 years, earnings by 20.6%, and reduced the probability of being incarcerated by 8 percentage points ( pp s). …”
mentioning
confidence: 99%
“…The “sustaining environments hypothesis” (Bailey et al, 2017) argues that ECE intervention effects may only persist when subsequent environments are of sufficient quality to build on gains made during the early program. Indeed, a number of recent studies have examined this hypothesis to mixed results (Ansari & Pianta, 2018; Bassok et al, 2018; Claessens et al, 2014; Jenkins et al, 2018; Johnson & Jackson, 2019; Zhai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that the gap in high school completion is eliminated when achievement is controlled for, suggests that interventions most likely to close the high school non-completion gap may be preschool interventions like the Perry preschool program and Head Start (Heckman, 2017) . Recent research suggests that these early education programs benefit from, and magnify the benefit of, access to high-quality schooling (Johnson & Jackson, 2019) . Reaffirming the value of early intervention, in research looking at children in Australia's Northern Territory, Silburn et al (2018) demonstrated a positive association between preschool attendance and attendance in the early years of primary school, which has a positive influence on NAPLAN outcomes.…”
Section: Comparing Equal Achieving Indigenous and Non-indigenous Youthmentioning
confidence: 99%